(untitled) (Itinera, 2023)
Landing on Earth. This now famous formula, which appears in the title of the exhibition/catalogue Critical Zones. The Science and Politics of Landing on Earth, curated by Bruno Latour and Peter Weibel, sums up Latour’s ecological-political project and his attempt to respond to the Anthropocene’s need to bring us back to Earth, to this unstable soil that reacts to our actions and from which the project of Modernity had progressively distanced us. For Latour, climate change and the definition of anthropos as a geological force impose the search for a new habitable territory: the Earth we thought we knew, but which now presents itself as a new terra incognita. However, because of the uncertainty about the shape of the Earth, the need to develop new tools to orient ourselves and describe the situation in which we find ourselves becomes more and more urgent. If what is at stake after the disorientation (spatial, temporal, identity) caused by Gaia’s intrusion is the re-politicization of belonging to the land, what are the cartographic representations that will be able to effectively describe our co-belonging to the space we inhabit, helping to make visible the different chains of agency? What are the tools we can use to learn to see things differently and thus become more “sensitive and responsive” to the fragile shells of this metastable world where life forms other than our own intersect their paths? What kind of map is an earthly map?